Uncovering genomic causes of co-morbidity in epilepsy: gene-driven phenotypic characterization of rare microdeletions. - Dalia Kasperavičiūtė; Claudia B Catarino; Krishna Chinthapalli; Lisa M S Clayton; Maria Thom; Lillian Martinian; Hannah Cohen; Shazia Adalat; Detlef Bockenhauer; Simon A Pope; Nicholas Lench; Martin Koltzenburg; et al. (PLoS ONE)
Background Patients with epilepsy often suffer from other important conditions. The existence of such co-morbidities is frequently not recognized and their relationship with epilepsy usually remains unexplained. Methodology/principal findings We describe three patients with common, sporadic, non-syndromic epilepsies in whom large genomic microdeletions were found during a study of genetic susceptibility to epilepsy. We performed detailed gene-driven clinical investigations in each patient. Disruption of the function of genes in the deleted regions can explain co-morbidities in these patients. Conclusions/significance Co-morbidities in patients with epilepsy can be part of a genomic abnormality even in the absence of (known) congenital malformations or intellectual disabilities. Gene-driven phenotype examination can also reveal clinically significant unsuspected condition.